PREDIKSI PRODUKSI MINYAK KELAPA SAWIT MENGGUNAKAN METODE FUZZY TSUKAMOTO DENGAN RULE YANG TERBENTUK MENGGUNAKAN DECISION TREE REPTREE - Tundo, Tundo (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2020)
Prediction of palm oil production using the Tsukamoto fuzzy method with the rules formed using REPTree decision tree is to speed up the making of the rules used without having to consult with experts. The results of the research analysis found the following conclusions: (1) The rule base model in this study is a decision tree that can be used for Tsukamoto's Fuzzy Inference System with an accuracy of 95.2381%, (2) Rule formed by 5 rules with a time of 0 seconds , (3) The results of direct analysis with real data in April, May, June, July, August, and September 2019 said that the error rate was 23.17% using the Average Forecasting Error Rate (AFER) error method, so the accuracy accuracy is 76.83% on the prediction of the amount of palm oil production.Â